Emotion, Sociality, and the Brain's Default Mode Network: Insights for Educational Practice and Policy. (October 2016) - Immordino-Yang, Mary Helen
Education research—for example, on character, stereotype threat, and identity-based motivation—demonstrates that social and emotional factors influence students' cognitive abilities and academic achievement. In parallel, recent advances in social-affective and cultural neuroscience reveal the social nature of human brain development and neural processing. Neuroscience can inform educational practice and policy by uncovering the mechanisms that may produce the observed social and emotional effects on learning. One major advance shows how the brain's Default Mode Network supports social-emotional feelings and broader thought patterns associated with self-processing, identity, meaning-making, and future-oriented thought. This article introduces policy makers to this research and its implications for educational decision making.